2014
DOI: 10.1016/j.physbeh.2014.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of energy status and diet on Bdnf expression in the ventromedial hypothalamus of male and female rats

Abstract: Sex differences exist in the regulation of energy homeostasis in response to calorie scarcity or excess. Brain-derived neurotrophic factor (BDNF) is one of the anorexigenic neuropeptides regulating energy homeostasis. Expression of Bdnf mRNA in the ventromedial nucleus of the hypothalamus (VMH) is closely associated with energy and reproductive status. We hypothesized that Bdnf expression in the VMH was differentially regulated by altered energy balance in male and female rats. Using dietary intervention, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 41 publications
2
32
1
Order By: Relevance
“…When comparing the absolute amount of BDNF in various brain regions between male and female, it is reported that female rats have higher BDNF content in the hippocampus, ventromedial hypothalamus, cortex and amygdala than male rats (Bakos et al 2009; Bland et al 2005; Liu et al 2014; Snigdha et al 2011). Franklin and Perrot-Sinal also demonstrated a lower level of BDNF in male hippocampus CA3 region (Franklin and Perrot-Sinal 2006).…”
Section: Sex Differences In Circulating Bdnf and Bdnf Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing the absolute amount of BDNF in various brain regions between male and female, it is reported that female rats have higher BDNF content in the hippocampus, ventromedial hypothalamus, cortex and amygdala than male rats (Bakos et al 2009; Bland et al 2005; Liu et al 2014; Snigdha et al 2011). Franklin and Perrot-Sinal also demonstrated a lower level of BDNF in male hippocampus CA3 region (Franklin and Perrot-Sinal 2006).…”
Section: Sex Differences In Circulating Bdnf and Bdnf Expressionmentioning
confidence: 99%
“…In a recent study, Liu et al . demonstrate a downregulation of BDNF expression in the male ventromedial hypothalamus (VMH) during fasting (Liu et al 2014). This observation concurs with the function of BDNF as an anorexic factor to suppress appetite in the hypothalamus (Pelleymounter et al 1995), which may be associated with the food intake behavioral change in response to food availability as male animals have a higher food-anticipatory activity and food intake after refeeding (Li et al 2015).…”
Section: Sex Differences In Circulating Bdnf and Bdnf Expressionmentioning
confidence: 99%
“…β-Actin cDNA was used as a control. Relative expression between a given sample and a reference sample was calculated using the 2 –ΔΔCt method [22]. …”
Section: Methodsmentioning
confidence: 99%
“…The chronic intracerebroventricular infusion of BDNF reduced the appetite and body weight of adult rats (Lapchak and Hefti, 1992), and the direct injection of BDNF into the VMH and PVN reduced food intake and increased energy expenditure (Wang et al, 2007a,b; Xu and Xie, 2016). In addition, 24 h food deprivation reduced the VMH BDNF mRNA levels of rats (Liu et al, 2014), and the injection of leptin, which is a potent anorectic factor derived from adipose tissue, increased the VMH BDNF mRNA levels of mice (Komori et al, 2006). These results suggest that hypothalamic BDNF is a potent anorectic factor and that the BDNF mRNA level might be partially regulated by leptin.…”
Section: Introductionmentioning
confidence: 99%